Use of Saline Water in Agriculture I. Description of the System - Dhir, R P; Bhatia, O P (Annals of Arid Zone, 2016)
Saline to highly saline sodic underground waters considered unsuitable for irrigation according to all available water quality classifications, are in use in western Rajasthan. The present paper, first in the series, presents some basic Information about the system of saline water irrigation in Pall district - an area where the system is most prevalent. Observations are based on data collected from thirty seven sites on water and soils characteristics, management practices and length since the well is in use. Data presented show that use or saline to highly saline and high sodium hazard waters is in vogue for many decades. The soils commanded with ’he e waters range widely in their texture and most or them have loam to clayey textures, with 60-90 em as the common depth. Lands irrigated with waters below 5.0 mmhos are generally double cropped whereas those with higher salinity are used in rotation with a fallow period of varying duration but extended mostly to 18 months in between for natural amelioration. Wheat variety ’Kharchia" is most common followed by barley. With waters below 5.0 mmhos raya, jowar and maize are also grown.